Evaluating the Coping Strategies among People Living with HIV/AIDS in Kaduna Central Senatorial District, Kaduna State, Nigeria - Ephraim Obadiah Dyages (Research Highlights in Disease and Health Research Vol. 2, 2023)
Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) is one of the most complicated and bewildering social challenges faced by contemporary societies because of its strong links to sexual and societal stigmatised behaviour. The purpose of this study is to evaluate the coping strategies among people living with HIV/AIDS (PLWHA) in Kaduna central senatorial district, Nigeria. The study was a cross section descriptive design. The instrument used was Brief COPE (Coping Orientation to Problems Experienced). Problem-focused coping strategies aim to amend or eliminate the causes of stress while emotion-focused coping strategies are meant to get by with the affective effects of the hassle. Using a multi-stage sampling technique, a sample of 407 participants who attended antiretroviral clinics was taken from four general hospitals within the district. The target population of 10,321 patients served as the basis for calculating the sample size. The study’s key findings showed that PLWHA use the problem-focused coping technique appropriately, with an overall mean of 2.61, and that most of them have been acting to try to improve the situation. The PLWHA also use the emotion focus coping strategy appropriately, with an overall average of 2.65, and the majority of them have received emotional support from others. However, the use of avoidance coping strategy was the most common, with an overall mean of 2.82, and the majority of them blamed themselves for the condition. The study revealed that problem and emotion focus were adequately used, while avoidance strategy was heavily used. It was therefore recommended that health workers use a variety of methods to educate the PLWHA, particularly on clinic days, on how to use problem-focused coping strategies in order to improve their quality of life.